Legal issues in electronic banking - Horn, Norbert (The Hague ; New York : Kluwer Law International, 2002)
Although electronic banking is rapidly overtaking direct bank-to-customer and bank-to-bank contact and seems to be moving forward without serious problems the law governing this telecommunication-based business is not always clearly defined in relation to certain issues that arise with ever-greater frequency, especially in cross-border transactions. Investigates and presents the applicable legal consensus for each of these important issues, based on existing legislation and relevant judicial decisions.
Includes index.
oif 02/03/15
Loans
Keywords: Electronic funds transfers; Electronic banking; Electronic banking - legal issues